2017
DOI: 10.1002/slct.201702086
|View full text |Cite
|
Sign up to set email alerts
|

Syn/Anti Pair of Triazole‐Bridged Cryptophanes: Synthesis, Characterization with Crystal Structures

Abstract: A pair of triazole bridged-cryptophanes have been synthesized by template method. The two diastereomers of the cryptophane, syn-and anti-isomers were isolated and characterized using NMR and Mass spectroscopy. Further confirmation of stereo-chemical configuration was done using Single Crystal analysis. The syn isomer was shown to encapsulate tetraethyl ammonium cation suggested by NMR, HRMS and confirmed by crystal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Syn and anti‐isomers of a cryptophane with triazole containing linker is reported earlier by our group [24] . A template approach was followed where vanillyl alcohol groups are appended to CTG derivative utilizing click reaction to form pre‐cryptophane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syn and anti‐isomers of a cryptophane with triazole containing linker is reported earlier by our group [24] . A template approach was followed where vanillyl alcohol groups are appended to CTG derivative utilizing click reaction to form pre‐cryptophane.…”
Section: Methodsmentioning
confidence: 99%
“…Syn and anti-isomers of a cryptophane with triazole containing linker is reported earlier by our group. [24] A template approach was followed where vanillyl alcohol groups are appended to CTG derivative utilizing click reaction to form precryptophane. Finally, it was cyclized intramolecularly using boron trifluoride-diethyl etherate in dry acetonitrile (See supporting information Scheme S1).The linker with a triazole ring has eight atoms in the chain.…”
mentioning
confidence: 99%
“…Purohit et al reported the synthesis of triazole-bridged cryptophanes by using the CuI-catalyzed click reaction (Scheme 10). [59] The synthesis was first attempted via the coupling approach, for which two CTB units tripropargyl-CTB 65 and triazide-CTB 67 were prepared from 1. The CTBs 65 and 67 were subjected to click reaction conditions aimed at generating the triazole-bridged cryptophane.…”
Section: Synthesis Of Cryptophanes By the Template Methodsmentioning
confidence: 99%
“…In the past, these molecules have received a lot of attention because they can accommodate different atoms or molecules within their cavity. For example, it has been shown that neutral (methane, xenon, halogenomethanes) or charged (alkali cations, ammonium, anions) species can easily enter the cavity of these host molecules, depending on the cavity size and the nature of the substituents grafted on to the benzene rings , . Interestingly, the encapsulation process strongly modifies the physical properties of both the guest and host molecules, thus leading to important spectroscopic changes.…”
Section: Introductionmentioning
confidence: 99%